New Member States of the EU: Current Trends in Regional Disparities - Josef Abrham; Milan Vosta (European Regional Science Association (ERSA), 2006)
The main aim of the article is, on the basis of a complex evaluation of regional developing factors, to formulate developing presumptions of the Czech Republic and selected new member states of the EU (Hungary, Poland and Slovakia) after their joining the European Union and therefore to appraise the impacts of the integrative process on a regional differentitaton of analyzed countries. The other aims of the study are: To set and adopt a methodical process for an evaluation of growth potential of the regions. To overall evaluate weaknesses in a regional structure of appraised countries of the Central Europe and main shortages from regional growth factors facilities point of view. To formulate convergent possibilities of examined countries regions after their joining the European Union considering the core of the European Union as well as the inside of the countries themselves. To analyze important theoretical concepts of regional development particularly with concentration on determination of main factors of regional growth. The starting point for the analyses of the regional disparities is the analyses of economic issues, demographic differentiation and its socioeconomic impact. At the same time new macroregions with stagnant economies were delinated, but also, dynamically developing regions which often spill over state bordes. In the article late development of regional disparities among regions of Czech republic and selected member states of the EU is also evaluated. This development is defined on the basis of own calculations of statistic indicators of variability. The evaluation of disparities is narrowed to the most important indicator of an economic level – GDP per capita. The basic statistic indicator for a comparison of differences is the Coefficient of Variance. The calculations of a range among regions have been included as additional. The conclusions are focused, in accord with determined aims of the study, on a complex evaluation of growth presumptions of regions of the Czech Republic and selected new member states of he EU after their joining the European Union as well as on formulation of main conclusions in relation to the evaluation of: typical trends in regional differentiations of analyzed countries, possibilities of regional growth after joining the European Union, presumptions of convergence of the average of current member states of EU, weaknesses examined regions from growth factors facilities point of view.
Keywords: 330